2023
DOI: 10.3389/fcvm.2023.1132893
|View full text |Cite
|
Sign up to set email alerts
|

Association of myocardial iron deficiency based on T2* CMR with the risk of mild left ventricular dysfunction in HIV-1-infected patients

Abstract: ObjectivesThis study sought to noninvasively determine myocardial iron levels in HIV-1-infected patients using CMR and explore the association between T2* values and mild left ventricular systolic dysfunction (LVSD).MethodsThis prospective study was conducted from June 2019 to July 2021. HIV-1-infected adults and healthy controls were consecutively enrolled for CMR exam. CMR exam included the assessment of myocardium iron content (T2*), cardiac function (cine), inflammation (T2), and fibrosis (through extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Chronic anemia, whether occurring independently or in conjunction with other comorbidities, is associated with adverse outcomes [ 7 , 127 ]. A study by Yan et al (2023) demonstrated that inflammation correlated positively with iron deficiency anemia and increased the risk for mild left ventricular systolic dysfunction [ 128 ]. Studies consistently emphasize that the presence of dysfunctional red blood cells (RBCs) in anemic conditions significantly contributes to the exacerbation of cardiovascular disease (CVD) severity [ 129 , 130 ].…”
Section: Chronic Anemia In Hiv Is Associated With Chronic Kidney Dise...mentioning
confidence: 99%
“…Chronic anemia, whether occurring independently or in conjunction with other comorbidities, is associated with adverse outcomes [ 7 , 127 ]. A study by Yan et al (2023) demonstrated that inflammation correlated positively with iron deficiency anemia and increased the risk for mild left ventricular systolic dysfunction [ 128 ]. Studies consistently emphasize that the presence of dysfunctional red blood cells (RBCs) in anemic conditions significantly contributes to the exacerbation of cardiovascular disease (CVD) severity [ 129 , 130 ].…”
Section: Chronic Anemia In Hiv Is Associated With Chronic Kidney Dise...mentioning
confidence: 99%